Ecosystem Service Assessments in Water Policy Implementation: An Analysis in Urban and Rural Estuaries - Schernewski, Gerald; Paysen, Philipp; Robbe, Esther; Inácio, Miguel; Schumacher, Johanna (Frontiers in Marine Science, 2019)
Coastal waters provide a wide range of ecosystem services (ES), but are under intensive human use, face fast degradation and are subject to increasing pressures and changes in near future. As consequence, European Union (EU) water policies try to protect, restore and manage coastal and marine systems in a sustainable way. The most important EU directive in this respect is the Water Framework Directive (WFD) (2000/60/EC). Objective is to reach a 'good status' in EU waters, following a stepwise and guided process. Our major objective is to test how an ecosystem service assessment can support WFD implementation in practice. We use the Marine Ecosystem Service Assessment Tool (MESAT) that utilizes spatial definitions, reference conditions and the good status according to the WFD as well as data and information gained during the implementation process. The data-based tool allows comparative analyses between different ecological states and an evaluation of relative changes in ES provision. We apply MESAT to two contrasting systems in the German Baltic Sea region, the rural Schlei and the urban/industrialized Warnow Estuary. These data-based assessments show how the ES provision has changed between the historic, pre-industrial state around 1880 (reference conditions with high ecological status), the situation around 1960 (good ecological status), and today. The analysis separates the estuaries into water bodies. A complementary expert-based ES assessment compares the situation today with a future scenario ‘Warnow 2040’ assuming a good ecological status as consequence of a successful WFD implementation. Strengths and weaknesses of the approaches and their utilization in the WFD are discussed. ES assessments can be regarded as suitable to support public relation activities and to increase the acceptance of measures. Further, they are promising tools in participation and stakeholder processes within the planning of measures. However an ES assessment not only supports the WFD implementation, but the WFD provides a frame for ES assessments larger scale assessments in seascapes, increases the acceptance of the ES approach and the readiness of stakeholders to get involved.